INCREASING CROP YIELD BY MYCORRHIZATION OF THE ROOT SYSTEM - Dymytrov, С.; Sabluk, В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The purpose of the research was to reveal the effect of mycorrhization of the root system of crops on their yield. Based on the results of research carried out in the years 2017–2021, it was found that mycorrhization of the root system of crops contributes to a significant increase in the yield of soft winter wheat, corn (Zea mays), sunflower, and soybean. Pre-seeding treatment was carried out in the shade (to avoid direct sunlight) by spraying with (or soaking in for two hours) a working solution on the day of sowing. Seed treatment was performed by manual using a sprayer. In particular, when using mycorrhizal fungi Tuber melanosporum Vittad. (bio preparation Mycovital), Trichoderma harzianum Rifai. (bio preparation Mycofriend), and bacteria Bacillus subtilis Cohn. (bio preparation Florobacillin) for pre-sowing seed treatment, the grain yield of soft winter wheat increased by 7.4–22.3 % as compared to the control. The yield of corn, sunflower, and soybean was also significantly higher than in the control. Thus, the yield of grain in all experimental treatments was higher as compared to control, specifically by 19.3–39.4 % in corn, by 24.4–43.5 % in sunflower, and by 16.4–37.7 % in soybean. The positive effect of Mycofriend (Trichoderma harzianum Rifai.) on the yield of all the studied crops was especially noticeable, with a yield increase of 22.3–43.5 %. In the treatments with other bio preparations (Mycovital and Florobacillin), the yield of the studied crops was slightly lower than in treatments with Mycofriend. Nevertheless, the yield increase was enough convincing. To conclude, the use of mycorrhizal fungi and nitrogen-fixing bacteria contributes to a significant increase in the yield of crops.